The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.2196/41148
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Expressing Empathy/Autonomy Support Using a COVID-19 Vaccination Chatbot: Experimental Study in a Sample of Belgian Adults

Abstract: Background Chatbots are increasingly used to support COVID-19 vaccination programs. Their persuasiveness may depend on the conversation-related context. Objective This study aims to investigate the moderating role of the conversation quality and chatbot expertise cues in the effects of expressing empathy/autonomy support using COVID-19 vaccination chatbots. Methods This experiment with 196 Dutch-speaking adu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(97 reference statements)
1
3
0
Order By: Relevance
“…The significance of empathy in fostering trust and rapport with users, as discussed by Warren-Smith (2023), Trzebiński et al (2023), andLtifi (2023), resonates with our observations (Ltifi, 2023;Trzebiński et al, 2023;Warren-Smith, 2023). The empathetic responses delivered by chatbots are pivotal in enhancing user engagement and satisfaction, a finding further supported by the role of empathy in service recovery contexts, as outlined by Fan (2023) (Fan, 2023).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The significance of empathy in fostering trust and rapport with users, as discussed by Warren-Smith (2023), Trzebiński et al (2023), andLtifi (2023), resonates with our observations (Ltifi, 2023;Trzebiński et al, 2023;Warren-Smith, 2023). The empathetic responses delivered by chatbots are pivotal in enhancing user engagement and satisfaction, a finding further supported by the role of empathy in service recovery contexts, as outlined by Fan (2023) (Fan, 2023).…”
Section: Discussionsupporting
confidence: 84%
“…Empathy, as a cornerstone of effective communication and rapport-building, has been extensively documented for its critical role in enhancing user engagement and trust in AI interfaces (Ltifi, 2023;Trzebiński et al, 2023;Warren-Smith, 2023). The deliberate incorporation of empathetic responses by chatbots not only elevates the user experience but also fosters a sense of connection and personalization, factors increasingly recognized as vital for user retention in competitive industries such as tourism (Fan, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While this theme issue in the Journal of Medical Internet Research titled "Chatbots and COVID-19" [12] focuses on chatbots related to COVID-19, the span of topics covered by these chatbots is broad. They range from vaccine hesitancy and equity in access to relevant information [13][14][15] to pandemic-related mental health [16][17][18][19]. A number of topics focus on health promotion interventions, such as smoking cessation [20], as well as encouraging physical activity [21] and tooth-brushing [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is a key predictor of prosocial behavior and social bonding. Research indicates that empathic concern can influence emotional and psychological well-being in significant ways (Tarlow & Greca, 2020;Trzebiński et al, 2023;Tullett & Plaks, 2016;Yadav & Iqbal, 2009;Zhai & Wibowo, 2022). For instance, Berry et al (2018) found that mindfulness increases prosocial responses toward ostracized strangers through heightened empathic concern, highlighting its importance in social contexts (Berry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%